Global warming and negative effects of degradation cryolithozone on buildings and structures - Nyamdorj Setev (Theoretical Hypotheses and Empirical Results, 2023)
Permafrost soils, common in vast areas of the world, are actively degrading and disappearing under the influence of modern global warming. Under the influence of the latter, many buildings and structures built according to the first principle of construction on permafrost soils (principle I - permafrost soils of the base are used in a frozen state, preserved during the construction process and throughout the entire period of operation of the structure), received deformations during the loss of stability of the base, which affects the safety of structures and ensuring their normal operational requirements. As an example of such cases, the results of complex soil studies at the base of a building in the suburbs of Ulaanbaatar, the city of Nalaikha in Mongolia, are considered. As a result of the research, it was found that the cause of the formation of vertical cracks and horizontal cavities is the degradation of permafrost due to global warming